ANALISA ISU WARNA KULIT PUTIH KOREA DALAM KONSTRUKSI KECANTIKAN IDEAL PADA IKLAN KOREA GLOW YUZU - Nurul Huda (2021)
Beauty is the most important thing for a women. The standards of beauty makes many women want to changes their appearance to looks more beauty. The development of technology and information makes beauty standard concept in Indonesia is having a Korean white skin. Korea Glow Yuzu Commercial is an advertisement that constructing audience in particularly women to having glowing and white skin like Korean women. Korea Glow Yuzu Commertial identified ideal of beauty as Korean women's white skin. This study was conducted to explore and identify the construction of Korean's White Skin in Korean Glow Yuzu advertisements by analyzing using qualitative methods and Roland Barthes' Semiotics approachment. The construction signs found in Korea Glow Yuzu advertising scenes are analyzed into the denotation, connotation and myth meaning. According to the findings, the Korean Glow advertisement featured a Korean white construction, and the Korean Glow Yuzu advertisement featured a beautiful and white female model.The meaning of the connotation is seen in the appearance of female models who want to highlight their white skin as well as their happy expressions because they have bright white skin. The white myth itself is related to social status. This study concludes that the Korean Glow Yuzu advertisement invites Indonesian women to have white skin like Korean women because, by having white skin, women can be said to be beautiful.